Nourishing and protecting our urban 'green' space in a post-pandemic world. (September 2020) - Rodgers, Christopher
'Green spaces' provide important cultural ecosystem services in our towns and cities. 'Green' space may come in many forms – for example parks, village greens, urban commons, or just neglected and undeveloped wasteland. But all of it is important as it can provide much needed space for open air recreation and exercise in crowded urban areas. The covid-19 pandemic and associated lockdown has shown just how important it is for us to have easy access to open space for recreation and exercise. But much of our green space is, in an age of austerity, under threat. Covid-19 has shown that we need to reappraise planning policy for the designation and protection of new areas of green space in our urban environment; to better protect existing open space, including village greens and commons; and to seek to rebalance planning policy to ensure that the drive for new housing does not take place at the expense of ensuring that adequate green space is provided for existing and future communities.